The Study of Balaghah in the Verse of Jihad: QS Al-Hajj verses 39-40 and QS Al-Baqarah verse 190 - -, Isnainiyah - (Faculty of Education and Teachers Training of UIN Sayyid Ali Rahmatullah Tulungagung, 2021)
The purpose of this study is to avoid errors in the intended meaning of the speaker delivered to the interlocutor about the jihad verse, explain the semantic rationality of the meaning of the jihad verse, study the style of language which is a method of delivering meaning in the jihad verse, and learn some models of the beauty of stylistics, and the beauty of the sentences used in the jihad verse. Researchers use descriptive methods with a content analysis model (content analysis) that discusses in-depth information obtained and records messages systematically which are then interpreted. The results of balaghah analysis from the Qur'an Surah Al-Hajj verses 39, 40 and Qur'an Surah al-Baqarah verse 190 explain the acts of terrorism committed by some people in the name of Islam, are not justified because they do not have a cause, and the level of crime that has been determined by religion, and because the object being fought is not in accordance with the provisions of religion, and is too far beyond the limit.